Men in primary healthcare: discussing (in)visibility based on gender perspectives - Márcia Thereza Couto; Thiago Félix Pinheiro; Otávio Valença; Rosana Machin; Geórgia Sibele Nogueira da Silva; Romeu Gomes; Lilia Blima Schraiber; Wagner dos Santos Figueiredo (Faculdade de Medicina de Botucatu (Unesp), 2010)
This paper presents an ethnographicstudy on the relationship between menand primary healthcare in eight clinics infour Brazilian states. The objective was tocomprehend the (in)visibility of menwithin the daily routine of care, based ongender perspectives, with discussion ofthe mechanisms that favor inequalities inhealthcare work. Different dimensions ofmale (in)visibility were identified withinthis context: targeting of men ininterventions within the field of publichealthcare policies; male users who facedifficulties in seeking attendance;difficulty in stimulating effectiveparticipation among men; and malesubjects of care (for themselves and forothers). The paper emphasizes theimportance of gender studies and theirrelationship with health, while discussingthe production of social inequalities thatare (re)produced by the genderinequalities that are present in the socialimaginary and in healthcare services.